2018
DOI: 10.4103/aam.aam_50_17
|View full text |Cite|
|
Sign up to set email alerts
|

Acute ischemic stroke thrombolysis with tenecteplase: An institutional experience from South India

Abstract: Objective:Outcome assessment of intravenous (IV) thrombolysis with tenecteplase in acute ischemic stroke.Materials and Methods:We consecutively enrolled acute ischemic stroke patients who underwent IV thrombolysis with tenecteplase from October 2016 to May 2017. Primary clinical efficacy outcome was defined as an improvement in the National Institute of Health Stroke Scale (NIHSS) score of ≥4 points at 24 h (h). Secondary clinical efficacy outcome was the favorable outcome on modified Rankin scale at 90 days d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…Post therapy improvements in primary outcomes and secondary outcomes were comparable to other studies. 11 Our study showed positive correlation of age with post treatment scores which helped predict outcome and this agrees to study results of young stroke by Owais et al 12 It suggests that the results holds true even for the adult population that there is poorer response to tenecteplase with advancing age. Another interesting observation was the significant improvement in mean mRS scores in the moderate strokes when compared to the higher degree strokes which as a matter of fact showed mild worsening which points to the fact that there is a very significant delayed treatment improvement in moderate stroke group with tenecteplase.…”
Section: Discussionsupporting
confidence: 90%
“…Post therapy improvements in primary outcomes and secondary outcomes were comparable to other studies. 11 Our study showed positive correlation of age with post treatment scores which helped predict outcome and this agrees to study results of young stroke by Owais et al 12 It suggests that the results holds true even for the adult population that there is poorer response to tenecteplase with advancing age. Another interesting observation was the significant improvement in mean mRS scores in the moderate strokes when compared to the higher degree strokes which as a matter of fact showed mild worsening which points to the fact that there is a very significant delayed treatment improvement in moderate stroke group with tenecteplase.…”
Section: Discussionsupporting
confidence: 90%
“…According to Owais et al 71% of the patients were men and their mean age was 60.7 years [20]. Also, Gioia et al stated that among 60 patients with ischemic stroke, 67% were men and their mean age was 73.5 years [21].…”
Section: Discussionmentioning
confidence: 98%
“…We found hypertension as the most common comorbidity (n=235, 64.7%). Other studies mentioned diabetes mellitus and hyperlipidemia in addition to hypertension as common risk factors in AFAIS patients [15,20,22].…”
Section: Discussionmentioning
confidence: 99%
“…The comparative studies comprised 9 RCTs 2-4,12,14-18 (that included 3699 patients), 1 prospective, observational cohort study 19 (that included 50 patients) and 6 retrospective, observational cohort studies 10,[20][21][22][23][24] (that included 2614 patients). The 10 noncomparative studies comprised 2 RCTs (1 that compared 2 doses of tenecteplase with each other 11 and 1 that compared tenecteplase with usual care excluding thrombolysis; 25 total 588 tenecteplase-treated patients), 5 prospective, interventional studies (reported in 4 articles; [26][27][28][29] total 266 tenecteplase-treated patients), 2 prospective, observational studies 30,31 (total 126 tenecteplase-treated patients), and 1 retrospective, observational study 32 (total 570 tenecteplase-treated patients). Most studies included participants treated via a timebased threshold for thrombolytic administration.…”
Section: Study Characteristicsmentioning
confidence: 99%